Combining Metabolic Engineering and Multiplexed Screening Methods for 3-Hydroxypropionic Acid Production in Pichia pastoris - Fina, Albert; Heux, Stephanie; Albiol, Joan; Ferrer, Pau (Frontiers in Bioengineering and Biotechnology, 2022)
Production of 3-hydroxypropionic acid (3-HP) in Pichia pastoris (syn. Komagataella phaffii) via the malonyl-CoA pathway has been recently demonstrated using glycerol as a carbon source, but the reported metrics were not commercially relevant. The flux through the heterologous pathway from malonyl-CoA to 3-HP was hypothesized as the main bottleneck. In the present study, different metabolic engineering approaches have been combined to improve the productivity of the original 3-HP producing strains. To do so, an additional copy of the gene encoding for the potential rate-limiting step of the pathway, i.e. the C-terminal domain of the malonyl-CoA reductase, was introduced. In addition, a variant of the endogenous acetyl-CoA carboxylase (ACC1S1132A) was overexpressed with the aim to increase the delivery of malonyl-CoA. Furthermore, the genes encoding for the pyruvate decarboxylase, aldehyde dehydrogenase and acetyl-CoA synthase, respectively, were overexpressed to enhance conversion of pyruvate into cytosolic acetyl-CoA, and the main gene responsible for the production of the by-product D-arabitol was deleted. Three different screening conditions were used to classify the performance of the different strains: 24-deep-well plates batch cultures, small-scale cultures in falcon tubes using FeedBeads® (i.e., slow release of glycerol over time), and mini bioreactor batch cultures. The best two strains from the FeedBeads® screening, PpHP8 and PpHP18, were tested in bioreactor fed-batch cultures using a pre-fixed exponentially increasing feeding rate. The strain PpHP18 produced up to 37.05 g L-1 of 3-HP at 0.712 g L-1 h-1 with a final product yield on glycerol of 0.194 Cmol·Cmol-1 in fed-batch cultures. Remarkably, PpHP18 did not rank among the 2-top producer strains in small scale batch cultivations in deep-well plates and mini bioreactors, highlighting the importance of multiplexed screening conditions for adequate assessment of metabolic engineering strategies. These results represent a 50% increase in the product yield and final concentration, as well as over 30% increase in volumetric productivity compared to the previously obtained metrics for P. pastoris. Overall, the combination of glycerol as carbon source and a metabolically engineered P. pastoris strain resulted in the highest 3-HP concentration and productivity reported so far in yeast.